Effects of seasonal grazing on plant species diversity and vegetation structure in a semi-arid ecosystem - Metzger, K.L.; Coughenour, M.B.; Reich, R.M.; Boone, R.B. (Journal of arid environments, 2005)
In evolutionary time frames, grazing by domesticated livestock on the short grass plains of East Africa is a new occurrence resulting in increased animal densities year around and modification to annual timing of grazing. We addressed the following questions: (1) do plant species diversity and vegetation structural differences exist between an area that is grazed only during the wet season and an adjacent area that is grazed year around; and, (2) does plant species diversity and structure correlate temporally with density of grazers? A spatially explicit ecosystem model was used to determine grazer densities. The two areas were similar with respect to grazer density during the wet season but not in the dry season. Dry season grazer densities were solely due to the presence of domesticated livestock. No significant differences in plant species diversity (H’), evenness, or richness were found between the two areas. However, the relative abundance of forbs, shrubs, percent cover of shrubs and bare ground was positively correlated with grazer densities during the dry season.